Remote intracerebral haemorrhage post intravenous thrombolysis: Experience from an Australian stroke centre. Issue 2 (February 2015) - Gao, Yuan; Churilov, Leonid; Teo, Sarah; Yan, Bernard
Abstract Remote intracerebral haemorrhage (rICH) is defined as intracerebral haemorrhage (ICH) post thrombolysis in brain regions without visible ischaemic changes. There is uncertainty that clinical outcomes and risk factors for rICH are different to those for local ICH. We investigated the morbidity, mortality and factors associated with rICH. We hypothesised that a previous history of cerebral ischaemic events is associated with increased risk of rICH. We included consecutive acute ischaemic stroke patients from 2003 to 2012 who were treated with intravenous thrombolysis. Clinical data included demographics, stroke classification, vascular risk factors and laboratory results. Clinical outcome was defined by modified Rankin Scale (mRS) score at 3 months. Baseline and follow-up CT scans were analysed for all ICH, and further dichotomised to rICH and local ICH. Clinical outcomes between rICH and local ICH were compared after adjustment for confounding factors. Four hundred and two patients were included in the study. The median age was 71 (interquartile range 60–79) years, and 54% were male. ICH (local ICH and rICH) was detected in 21.6% (87/402) of all patients post thrombolysis. The incidence of rICH was 2.2% (9/402). Most rICH were classified as haemorrhagic infarct category 2 (HI2) (p = 0.002). The proportion of patients with previous transient ischaemic attacks was significantly higher in the rICH group (33.33% versus 2.56%; odds ratio [OR] 18.75, 95% confidence interval [CI] 3.06–114.38; p = 0.007). The proportion of mRS scores 0–2 at 3 months was significantly higher in the rICH group (50% versus 28%; adjusted OR 10.469, 95%CI 1.474–74.338; p = 0.019). The 3 month mortality rate was 22.2% (2/9) in the rICH group and 36% (27/75) in the local ICH group (OR 0.53, 95%CI 0–2.51, p = 0.703). rICH was an infrequent complication after intravenous thrombolysis in our series. The clinical outcome of rICH was significantly better than local ICH. Of note, previous episodes of transient ischaemic attack were significantly higher in the rICH group, suggesting previous ischaemic injury as an underlying mechanism.